Financial Performance and Share Prices of Banks of State-Owned Enterprises in Indonesia - Nureny Nureny (Program Pascasarjana Universitas Negeri Makassar, 2019)
This study aims to examine the effect of financial performance, namely; Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA) and Operational Cost on Operational Income (BOPO) on stock price of state-owned Bank in Indonesia. The sample in the study is state-owned Bank registered at Indonesia Stock Exchange and still listed until 2018 namely; Bank Mandiri, Bank Negara Indonesia (BNI), Bank Tabungan Negara (BTN), and Bank Rakyat Indonesia (BRI). The collection of data is carried out by documentation technique. Technique employed in analyzing data is multiple regression analysis. The results found that (1) Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA) and Operational Cost on Operational Income (BOPO) simultaneously affect stock price of state-owned Bank in Indonesia. (2) Partially, NIM, NPL, LDR, ROA, BOPO variables have an insignificant effect on stock price of state-owned Bank that already have gone public on Indonesia Stock Exchange. While CAR has a significant influence on stock price of state-owned Bank that already have gone public on Indonesia Stock Exchange. This accordingly provides an indication that stock price of a state-owned Bank in Indonesia is not predominantly determined by its financial performance, but by public's trust in state-owned Bank concerned.